QSAR Modeling of Mammal Acute Toxicity by Oral Exposure - Raevsky, O.A.; Grigorev, V.Yu.; Yarkov, A.V.; Tinkov, O.V. (Biomedical Chemistry: Research and Methods, 2018)
7490 organic compounds exhibiting acute oral toxicity in mice were studied. Regression models with satisfactory statistical characteristics have been created using the original AMP (arithmetic mean property) approach. The best models using the training and test sets were characterized by the squared linear correlation coefficient and the standard deviation of 0.5 and 0.45 (in log(1/LD50) units).